Early stimulation in babies and children with developmental problems: revisiting the topic (Research, Society and Development, 2022)
This article aims to present the importance of the Interdisciplinary Early Stimulation Clinic for babies and young children with developmental problems. Therefore, concepts such as child development and subjectivation in the first years of life were addressed, sharpening the look at the mismatch between the real child and parental ideals, in order to detect the first signs of possible problems in the development and maturation of babies and small children. The research presents how the clinical work is structured, having as central points the intervention from playing and the affiliation process. It is pointed out that the Interdisciplinary Clinic in Early Stimulation prioritizes the support of the parent-infant bond, promoting the support that the child needs for their development.